Strategi Pola Asuh Digital untuk Mendukung Perkembangan Sosial, Emosional, dan Spiritual Anak Usia 4-12 Tahun - Kurniadi, Endrian; Saimah (Bayani, 2024)
Digital technology has transformed the way children grow and learn, presenting new challenges in parenting. This study aims to investigate the role of interpersonal communication in managing children's use of digital technology and its impact on their social, emotional, and spiritual development. Using a qualitative approach, this study involved 20 parents with children aged 4-12 years in Kota Nunukan. Data were collected through in-depth interviews and direct observations, which were then analyzed using content analysis methods. The results showed that open and empathetic communication between parents and children is crucial in managing the use of digital technology. Parents who actively communicate with their children tend to see more positive social, emotional, and spiritual development. Strategies used include setting screen time limits, engaging in children's digital activities, and educating about digital ethics and online safety. The study also found that integrating spiritual values into children's use of technology can support better character development. The conclusions of this study affirm that effective interpersonal communication between parents and children, as well as the integration of spiritual values, can have a positive impact on children's development in the digital age. Practical implications of these findings include guidelines for parents, educators, and policymakers to create an environment that supports healthy and responsible use of technology.